Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 3 czerwca 2016 roku, sygn. akt II FSK 1209/14 - Lewandowski, Mateusz (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The author conducts an analysis of the judgment of the Supreme Administrative Court of 3 June 2016, case No II FSK 1209/14 In following sections author analyzes differences between the concept of declaration of will and the concept of act in law - the occurrence of the declaration of will causes a duty to bear a compulsory pecuniary. The gloss points out the inability to adjudge notary public as a tax on civil law transactions remitter in this case. In this article author criticizes also the incorrect consideration of the Supreme Administrative Court concerning the moment of arising of a tax obligation
Keywords: podatek od czynności cywilnoprawnych; zobowiązanie podatkowe; czynność prawna; oświadczenie woli; notariusz